Peran pendidikan kewarganegaraan dalam membentuk identitas nasional di kalangan pelajar - Farodis, Maiya (Maliki Interdisciplinary Journal, 2025)
Developments and changes in digital technology have had a significant impact on the dynamics of national identity, as well as being a challenge to the stability of national values ​​in multicultural Indonesian society. This national article aims to analyze the role of Citizenship Education in responding to global challenges and digitalization on identity formation among students. Using a qualitative descriptive approach based on literature studies, this research examines the transformation of the citizenship curriculum through updating national values, a reflective pedagogical approach, and strengthening the role of teachers and educational institutions. The focus of the study includes inequality in the implementation of citizenship education, the influence of global media on the younger generation, and the role of education in maintaining the sovereignty of national values. The results of the analysis show that the citizenship curriculum functions as a strategic tool for internalizing adaptive and inclusive nationalism amidst the onslaught of global identities. The importance of cross-sector collaboration, digital literacy and learning innovation was also emphasized to build strong and contextual national awareness. This article recommends continuous curriculum updates and participatory education policies to strengthen the position of national identity in the global and digital era.